2020
DOI: 10.5588/pha.20.0020
|View full text |Cite
|
Sign up to set email alerts
|

Choice architecture-based prescribing tool for TB preventive therapy: a pilot study in South Africa

Abstract: Background: All people with HIV who screen negative for active tuberculosis (TB) should receive isoniazid preventive therapy (IPT). IPT implementation remains substantially below the 90% WHO target. This study sought to further understanding of IPT prescription by piloting a simplified prescribing approach.Setting: Primary care clinics in Matlosana, South Africa.Design: This was a mixed-methods implementation study.Methods: Nine providers were recruited and underwent training on 2018 WHO guidelines. A simplif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 20 publications
1
7
0
Order By: Relevance
“…The six articles that reported a perceived decrease in consultation duration suggested explanations which included reduced need for data entry [ 62 , 81 , 98 ], synchronisation with the usual workflow of decision-making [ 118 ] and saving time when discussing risk management of specific conditions during the consultation [ 67 , 68 ]. In terms of the purpose, feature and functionality of the studied eCDS tools, the articles referred mainly to tools that were seen to improve efficiency, four of which featured a tool designed to support clinicians in the management of conditions, rather than on their diagnosis.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The six articles that reported a perceived decrease in consultation duration suggested explanations which included reduced need for data entry [ 62 , 81 , 98 ], synchronisation with the usual workflow of decision-making [ 118 ] and saving time when discussing risk management of specific conditions during the consultation [ 67 , 68 ]. In terms of the purpose, feature and functionality of the studied eCDS tools, the articles referred mainly to tools that were seen to improve efficiency, four of which featured a tool designed to support clinicians in the management of conditions, rather than on their diagnosis.…”
Section: Resultsmentioning
confidence: 99%
“…Qualitative interview data suggested that clinicians felt an eCDS tool for prescribing tuberculosis preventive therapy decreased their cognitive workload during consultations. [ 98 ] This was perceived as advantageous as it reduced the amount of time spent documenting medications and their contraindications. However, in two articles, eCDS tools were noted to increase cognitive workload.…”
Section: Resultsmentioning
confidence: 99%
“…Qualitative interview data suggested that clinicians felt an eCDS tool for prescribing tuberculosis preventive therapy decreased their cognitive workload during consultations. 79 This was perceived as advantageous as it reduced the amount of time spent documenting medications and their contraindications. However, in two studies, eCDS tools were noted to increase cognitive workload.…”
Section: Methods To Measure Consultation Durationmentioning
confidence: 99%
“…The six studies that reported a perceived decrease in consultation duration referred mainly to eCDS tools that were seen to improve e ciency, four of which featured a tool designed to support clinicians in the management of conditions, rather than on their diagnosis. The rationale for reported improvement included reduced need for data entry [77][78][79] , synchronisation with the usual work ow of decision-making 80 and saving time when discussing risk management of speci c conditions during the consultation 58,81 . The tools described within these studies were all either embedded within the EMR system or linked/interacted with the EMR in some way.…”
Section: Perceived Increase In Consultation Durationmentioning
confidence: 99%
“…Over the past decade, these tenets of behavioral economics have been increasingly utilized in health care for both patients (cancer screenings [ 14 ], hospital appointment no-show rates [ 7 ], medication adherence for behavioral health [ 15 ], HIV testing rates [ 16 ], obesity and binge eating [ 17 ]) and clinicians (prescribing behavior [ 18 , 19 ], overtreatment of diabetes [ 20 ]), with 83 publications in the top 3 highest impact general medicine journals (Journal of the American Medical Association, The Lancet, The New England Journal of Medicine) from 1998 to 2018 [ 21 ]. A systematic review [ 22 ] found patient portal interventions to be effective in improving a few psychological outcomes, medication adherence, and preventive service use.…”
Section: Introductionmentioning
confidence: 99%